Extending Information On Museum Artefacts Through Augmented Reality: Indonesian National Museum Case - Bayu Prakoso Dirgantoro; Jude Joseph Lamug Martinez (Journal of Games, Game Art, and Gamification, 2016)
Jakarta has 62 well-maintained museums but most are still conventional in the way that they mostly display objects or collections with accompanying written information and interactive media is still very limited.[1] In Indonesia, museum curators and managers need to be more creative in presenting objects and information to increase the number of visitors [2].The difficulty of luring visitors to museums has even became a national issue and problem:[1] the Indonesian government considers it as a matter that needs to be addressed. [3, 4] In 2010, the Association of Museums in Indonesia (AMI) and the Ministry of Tourism and Creative Economy declared it the Year of Visiting the Museum [5] as part of the National Movement to Love Museums, which lasted until 2014 [1]. The strategic efforts from the Ministry of Tourism and Creative Economy were then followed up with the introduction of national programs such as Revitalizing Indonesian Museum [5]. Museums should be a place to enhance the learning experience, sharing knowledge, as well as a place to study and conduct research [5]. Here, the museum is required not only as a means of public learning, but must also be able to support the development of study centers in universities [5]. Therefore, adding interactive media using Augmented Reality to Indonesian museums will increase the interest in learning about the local culture and heritage of Indonesia among the Indonesian population, especially students.